HEXAHELIX COLLABORATION IN FLASH FLOOD DISASTER MANAGEMENT IN THE LAKE TOBA AREA - Sahrul Ramadhan; Audia Junita; Beby Masitho Batubara (Pena Cendekia Insani, 2026)
This study aims to analyze the governance of Hexahelix collaboration in the implementation of flash flood disaster management in the Lake Toba Area and to identify the constraints and obstacles encountered in its implementation. The research method used is descriptive qualitative, with data collection techniques through interviews, observations, and documentation. The research informants consisted of the Head of the Regional Disaster Management Agency (BPBD) of North Sumatra Province, the Head of the Cooperation, Control and Evaluation Division of BPBD North Sumatra Province, Staff of the Community and Environmental Empowerment Department of PT Inalum Hydropower, the Chair of the Pandawa Kayak Organization of North Sumatra, the Director of the Center for Climate Change and Disaster Mitigation Studies of the Faculty of Forestry, University of North Sumatra, and a journalist from Tribun Medan. The results of the study indicate that the role of the Regional Disaster Management Agency has been carried out in accordance with the concept of governance, where disaster management is no longer centered solely on the government but involves various actors within a collaborative framework. However, the implementation of Hexahelix collaboration has not been fully optimal, particularly in the pre-disaster phase, which still requires strengthened coordination, increased human resource capacity, and cross-sectoral program integration. Internal constraints include the limited number of disaster-certified personnel, while external constraints are related to the persistence of communities residing in flash flood–prone areas due to livelihood factors. This study recommends enhancing the capacity of disaster management personnel, strengthening scientific studies as a basis for policy, developing more integrated multisectoral collaboration, promoting development oriented toward disaster risk reduction, and increasing the transparency of information that is easily accessible to the public.